2015
DOI: 10.1371/journal.pone.0118470
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Video Game Cycling Leads to Higher Energy Expenditure and Is More Enjoyable than Conventional Exercise in Adults

Abstract: BackgroundDespite the widely accepted health benefits of regular physical activity, only a small percentage of the population meets the current recommendations. The reasons include a wide use of technology and a lack of enjoyment while exercising. The purpose of this study was to compare the physiological, perceptual and enjoyment responses between a single bout of (I) conventional cycling and (II) interactive cycling video game at a matched workload.MethodsA cross-sectional study in 34 healthy participants wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
30
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 44 publications
8
30
1
9
Order By: Relevance
“…It has been shown to be an enjoyable activity for adolescents, young adults and older adults, thereby having a potential for sustained activity participation 11 12. However, previous studies on the physiological responses to exergaming have found that such gaming elicited light-to-moderate exercise intensity 12–14…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to be an enjoyable activity for adolescents, young adults and older adults, thereby having a potential for sustained activity participation 11 12. However, previous studies on the physiological responses to exergaming have found that such gaming elicited light-to-moderate exercise intensity 12–14…”
Section: Introductionmentioning
confidence: 99%
“…Porém, devido à extensa variedade metodológica dos estudos existentes, pouco se sabe sobre quão próximos são os efeitos fisiológicos do jogo em EXG em relação às mesmas atividades realizadas de forma convencional. Hipotetiza-se que, apesar das atividades apresentarem demandas semelhantes, possam existir efeitos distintos, principalmente devido aos níveis de imersão e engajamento que tendem a ser mais altos em EXG, ao compará-los com atividades físicas convencionais 11 . Portanto, o objetivo deste estudo foi realizar uma revisão sistemática e metanálise sobre os efeitos fisiológicos agudos entre essas práticas de atividades descritas.…”
Section: Meta-analysis; Motor Activity; Video Games; Energy Expendituunclassified
“…As amostras selecionadas foram compostas por universitários 5,14,15,19 , adultos jovens 11,16,18,20,21 e escolares 17 . Com exceção do estudo de Haddock et al 17 , que foi realizado com escolares de 12,0 ± 1,2 anos, os demais estudos utilizaram sujeitos adultos com idades entre 20 ± 1,0 anos 21 Nesse contexto, quatro estudos compararam EXG de ciclismo com bicicleta estacionária convencional 5,11,15,19 , quatro compararam EXG de corrida com correr em esteira ou pista 14,17,20,21 . Ainda, um comparou EXG de boxe com treinar boxe em saco de pancadas 18 e um confrontou sessão de fisioterapia com EXG com sessão de fisioterapia convencional 16 .…”
Section: Características Das Intervençõesunclassified
See 1 more Smart Citation
“…Research results have shown that AVGs deemed more fun increase the length of participation and energy expenditure during AVG play [102]. When PA is viewed as entertaining, doable, relevant, and enjoyable, players enter into a flow state that result in increased energy expenditure and less perceived effort [103,104]. VOAGs allow for cooperative and competitive play over the Internet with others players enabling participants to engage in PA that expands the pool of participants from proximal to an online community of participants thereby increasing opportunities for participation.…”
mentioning
confidence: 99%